RECORDS MANAGEMENT IN THE IMPLEMENTATION OF STATE ADMINISTRATION AT THE EDUCATION AND CULTURE OFFICE OF BALANGAN REGENCY - Jamil Rifani; Riswandi Ahdiat; Yulida Trisnawati (PPPM STIA Amuntai, 2026)
This study aims to examine the implementation of records management and the factors influencing it at the Department of Education and Culture of Balangan Regency. The research employs a qualitative approach using a field research method, conducted through observation, documentation, and interviews with several key informants. The findings indicate that records management has been implemented relatively well through the application of official correspondence administration procedures, the use of classification codes, and employees’ awareness of the importance of proper document management. The main supporting factors include leadership commitment, employee discipline, and the utilization of applicable records management guidelines. However, the study also identifies several constraints, such as limited archival storage space, insufficient standard storage shelving, humid room conditions, and the suboptimal implementation of records retention and disposal processes in accordance with the Records Retention Schedule (JRA). In addition, archival training has not been conducted regularly, resulting in varying levels of human resource competency. This research underscores the importance of improving archival facilities and infrastructure, as well as strengthening employee capacity, to ensure that records management within the institution operates more effectively, efficiently, and in compliance with national standards.